2015
DOI: 10.2105/ajph.2014.302340
|View full text |Cite
|
Sign up to set email alerts
|

The Intended and Unintended Consequences of a Legal Measure to Cut the Flow of Illegal Cigarettes Into New York City: The Case of the South Bronx

Abstract: After the tax amendment, the supply of contraband cigarettes appears to have quickly shifted from one lower-priced jurisdiction to another without a change in the overall prevalence of contraband cigarettes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…36 Virginia is the most common source of cigarettes trafficked into New York City. 37 One study found that more than 80% of the illicit cigarettes found in the South Bronx are Newport menthol cigarettes, 38 a phenomenon that is also prevalent in Harlem. 39 In the event of a ban on menthol cigarettes, the supply for what is likely the most commonly bootlegged cigarette brand in New York City would evaporate, potentially resulting in an overall decrease in New York City's illicit market.…”
Section: Flood Of Unregulated Cigarettes On the Marketmentioning
confidence: 99%
“…36 Virginia is the most common source of cigarettes trafficked into New York City. 37 One study found that more than 80% of the illicit cigarettes found in the South Bronx are Newport menthol cigarettes, 38 a phenomenon that is also prevalent in Harlem. 39 In the event of a ban on menthol cigarettes, the supply for what is likely the most commonly bootlegged cigarette brand in New York City would evaporate, potentially resulting in an overall decrease in New York City's illicit market.…”
Section: Flood Of Unregulated Cigarettes On the Marketmentioning
confidence: 99%
“…In 2011, the Second Circuit confirmed that changes made to New York State’s tax laws in 2010 requiring that a tax stamp be affixed to all cigarettes applied to cigarettes sold on Native American reservations. 26 Several participants mentioned that they switched to reservation brand cigarettes when they could no longer purchase untaxed premium brands on the reservations.…”
Section: Resultsmentioning
confidence: 99%
“…25 Since 2011, cigarettes with stamps from low-tax states like Virginia have become the lower priced norm in NYC, while Native American reservation brands have been more widely used in other parts of the state. 16,25 -28…”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation
“…Data were obtained from focus groups with a purposive sample of self-identified smokers who reside in the South Bronx, which is a geographic area within a borough of New York City (the Bronx) with a high prevalence of illicit cigarettes, typically bootlegged from low-tax states like Virginia ( Chernick and Merriman, 2013 ; Kurti et al, 2015 ; Lovenheim, 2008 ; Shelley et al, 2007 ; von Lampe and Kurti, 2016 ; John and Ross, 2017 ).…”
Section: Methodsmentioning
confidence: 99%